Implementasi Speech Synthesis Berbasis Mobile untuk Pelestarian Cerita Rakyat dalam Dialek Melayu Kepulauan Meranti - Muhammad Zul Asfi; Muhammad Fikry; Yusra Yusra; Fadhilah Syafria; Siska Kurnia Gusti (TIN: Terapan Informatika Nusantara, 2026)
The preservation of Malay folklore faces serious challenges amid the increasing dominance of digital content. This study develops LinguaTales, an Android-based application featuring Malay folklore from the Meranti Islands that integrates Speech Synthesis (Text-to-Speech) technology to provide automated audio narration. The study aims to develop and evaluate LinguaTales while contributing to the preservation of the Meranti Malay dialect, which is increasingly marginalized. The system was developed using the Rapid Application Development (RAD) method with Kotlin in Android Studio. The folklore content was validated by the Malay Customary Institution of Riau (LAMR) Merbau District to ensure the accuracy of dialect vocabulary and cultural values. The application supports three languages (Malay, Indonesian, and English) through two TTS modes: online (Google TTS) and offline (ONNX VITS), supported by a lexical substitution preprocessing mechanism to address dialect vocabulary limitations. Usability testing using the System Usability Scale (SUS) involved 12 respondents, including children, teachers, and parents, resulting in an average score of 77.92 (Acceptable), while the teacher group achieved the highest score of 80.00 (Excellent). The results indicate that LinguaTales is suitable for all target users and contributes to the preservation of the Meranti Malay language and culture through accessible and sustainable digital technology. The proposed lexical substitution mechanism also provides a methodological contribution to the development of TTS systems for low-resource regional languages.